Efficacy and safety of ciprofol for sedation in outpatient gynecological procedures: a phase III multicenter randomized trial - Xu, Jing; Yang, Mengchang; Zeng, Yuan; Zou, Xiao-Hua; Ren, Jing-Hua; Xia, Zhongyuan; Xie, Hai-Hui; Yu, Yong-Hao; Xu, Ming-Jun; Chen, Wei; Wang, Dong-Xin (Frontiers in Medicine, 2024)
Objective: Ciprofol (also known as cipepofol and HSK3486), is a compound similar to propofol in chemical structure and hypnotic effect. Herein we evaluated the efficacy and safety of ciprofol for sedation in outpatient gynecological procedures.Methods: This phase III multicenter randomized trial with a non-inferiority design was conducted in nine tertiary hospitals. We enrolled 135 women aged 18-65 years who were scheduled for ambulatory gynecological procedures. Patients were randomly assigned to receive either ciprofol (0.4 mg/kg for induction and 0.2 mg/kg for maintenance) or propofol (2.0 mg/kg for induction and 1.0 mg/kg for maintenance) sedation in a 2:1 ratio. Patients and investigators for data collection and outcome assessment were blinded to study group assignments. The primary outcome was the success rate of sedation, defined as completion of procedure without remedial anesthetics. The non-inferiority margin was set at -8%. Secondary outcomes included time to successful induction, time to full awake, time to meet discharge criteria, and satisfaction with sedation assessed by patients and doctors. We also monitored occurrence of adverse events and injection pain.Results: A total of 135 patients were enrolled; 134 patients (90 patients received ciprofol sedation and 44 patients propofol sedation) were included in final intention-to-treat analysis. The success rates were both 100% in the two groups (rate difference, 0.0%; 95% CI, -4.1% to 8.0%), i.e., ciprofol was non-inferior to propofol. When compared with propofol sedation, patients given ciprofol required more time to reach successful induction (median difference [MD], 2 sec; 95% CI, 1 to 7; P<0.001), and required more time to reach full awake (MD, 2.3 min; 95% CI, 1.4 to 3.1; P<0.001) and discharge criteria (MD, 2.3 min; 95% CI, 1.5 to 3.2; P<0.001). Fewer patients in the ciprofol group were dissatisfied with sedation (relative risk, 0.21; 95% CI, 0.06 to 0.77; P=0.024). Patients given ciprofol sedation had lower incidences of treat-emergent adverse events (34.4% [31/90] vs. 79.5% [35/44]; P<0.001) and injection pain (6.7% [6/90] vs. 61.4% [27/44]; P<0.001).Conclusions: Ciprofol for sedation in ambulatory gynecological procedures was non-inferior to propofol, with less adverse events and injection pain.